Hybrid MDM-MIMO radio-over-free space optical system for high-capacity 5G and beyond networks under strong and weak scintillation - Chaudhary, Sushank; Khichar, Sunita; Saadi, Muhammad; Parniarifard, Amir; Sharma, Abhishek (Frontiers in Physics, 2025)
IntroductionThe increasing demand for high-capacity, low-latency communication in 5G and Beyond networks necessitates innovative solutions to overcome the limitations of conventional wireless technologies. Optical Wireless Communication (OWC) technologies, particularly Radio-over-Free Space Optical (RoFSO) systems, offer a promising approach to addressing spectrum congestion and environmental attenuation challenges.MethodsThis study presents a hybrid Mode Division Multiplexing (MDM)-Multiple Input Multiple Output (MIMO) RoFSO system operating at an 80 GHz·mm-wave carrier to achieve high-capacity data transmission. The system employs a Gamma-Gamma turbulence model to analyze performance under weak and strong scintillation conditions. Performance metrics such as Bit Error Rate (BER) and spectral efficiency are evaluated for different MIMO configurations (2 × 2 and 4 × 4) to assess link reliability and robustness.ResultsThe results demonstrate that MDM-MIMO configurations significantly enhance system performance, with the 4 × 4 MIMO setup exhibiting the lowest BER and superior signal quality over extended link distances. The system maintains reliable data transmission under weak and strong scintillation, showcasing its potential for high-speed wireless communication in challenging atmospheric conditions.DiscussionThe proposed hybrid MDM-MIMO RoFSO system provides a scalable and resilient solution for future wireless networks, including urban backhaul, emergency communication, and satellite-based optical links. While the technology offers substantial improvements in spectral efficiency and link reliability, practical deployment challenges such as hardware constraints, regulatory issues, and power consumption must be addressed to enable widespread adoption.ConclusionThis study highlights the effectiveness of MDM-MIMO RoFSO systems in enhancing the performance of high-capacity wireless communication. The findings contribute to the development of next-generation networks capable of meeting the stringent demands of future communication infrastructures.